2015
DOI: 10.1111/rode.12161
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Policy inChina after the Financial Crisis: Evidence from Time‐varying Exchange Rate Basket

Abstract: We analyze the period of a managed floating exchange rate policy in China between June 2010 and November 2014. We estimate a time-varying structure of a hypothetical currency basket using the Kalman filter. We show that the exchange rate policy continues to focus on the US dollar. However, its weight has been gradually declining, while this decline has moderated in 2014. The euro played some role before summer 2011, but became negligible after the outbreak of the European sovereign debt crisis. Finally, the Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In another paper, Cui (2014) found that the US dollar's weight had declined steadily since 2011 and that weights of the other currencies like the Singapore dollar were increasing, which indicated that the RMB was shifting from a dollar peg to a currency basket peg. Fidrmuc and Siddiqui (2014) also found a declining weight assigned to the US dollar.…”
Section: Introductionmentioning
confidence: 96%
“…In another paper, Cui (2014) found that the US dollar's weight had declined steadily since 2011 and that weights of the other currencies like the Singapore dollar were increasing, which indicated that the RMB was shifting from a dollar peg to a currency basket peg. Fidrmuc and Siddiqui (2014) also found a declining weight assigned to the US dollar.…”
Section: Introductionmentioning
confidence: 96%